2015
DOI: 10.2500/ajra.2015.29.4195
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Rutin through Regulation of Vascular Endothelial Growth Factor in Allergic Rhinitis

Abstract: The present study showed that A. hookeri or RU had an anti-allergic inflammatory effects. Analysis of these results indicated that A. hookeri and RU might protect against AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Furthermore, hypotension induced by histamine causes hypoxia in brain tissues [23], and hypoxic environments upregulate HIF-1α-responsive chemokines, such as VEGF, which is known to promote the recruitment and proliferation of endothelial progenitor cells, and, in addition, up-regulation of HIF-1 promotes new blood vessel development [24]. Increased vascular permeability is known to induce inflammatory responses via VEGF [25]. In our previous study, rutin exerted anti-allergic effects by suppressing VEGF expression [25]; in another study, hypoxia induced histamine synthesis and histidine decarboxylase expression via HIF-1 activation in mast cells [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hypotension induced by histamine causes hypoxia in brain tissues [23], and hypoxic environments upregulate HIF-1α-responsive chemokines, such as VEGF, which is known to promote the recruitment and proliferation of endothelial progenitor cells, and, in addition, up-regulation of HIF-1 promotes new blood vessel development [24]. Increased vascular permeability is known to induce inflammatory responses via VEGF [25]. In our previous study, rutin exerted anti-allergic effects by suppressing VEGF expression [25]; in another study, hypoxia induced histamine synthesis and histidine decarboxylase expression via HIF-1 activation in mast cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Increased vascular permeability is known to induce inflammatory responses via VEGF [25]. In our previous study, rutin exerted anti-allergic effects by suppressing VEGF expression [25]; in another study, hypoxia induced histamine synthesis and histidine decarboxylase expression via HIF-1 activation in mast cells [10]. In the present study, Buk music was found to inhibit systemic anaphylaxis and histamine release induced by compound 48/80, and to reduce the increases in HIF-1α and VEGF levels induced by anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used by locals to treat coughs, colds, wounds, and burn (Sharma, Gohil, & Kaul, ). Our previous study reported that AH alleviated clinical symptoms of allergic rhinitis in an animal model (Kim et al, ). Moreover, AH has an antimicrobial activity (Kim et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…Kim et al 14 reports that Allium hookeri has anti-inflammatory effects in these experimental models.…”
mentioning
confidence: 99%